Richard Dale papers - Dale, Richard, 1756-1826.
Correspondence, commissions, mathematics notebook, and journal/logbook (1787-1789) kept on a voyage aboard a merchant ship to Canton, China, and to New Guinea. Includes letterbook (1801-1802) of Dale's outgoing correspondence while in command of the USS President (Frigate) in the Mediterranean during the Tripolitan War; and letterbook of incoming correspondence (1780-1845) to Dale, to his son-in-law, Rear Admiral George C. Read, and to several others. Correspondents include William Bainbridge, John Paul Jones, John P. Kennedy, Robert Smith, and Benjamin Stoddert.
Microfilm edition of journal/logbook available
Microfilm produced from originals in the Manuscript Division.
Naval officer; served with the British navy from 1776 to 1777 when he joined the Continental Navy, serving as first lieutenant to John Paul Jones on the Bonhomme Richard.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bainbridge, William, -- 1774-1833 -- Correspondence; Jones, John Paul, -- 1747-1792 -- Correspondence; Kennedy, John Pendleton, -- 1795-1870 -- Correspondence; Read, George C. -- 1787-1862 -- Correspondence; Smith, Robert, -- 1757-1842 -- Correspondence; Stoddert, Benjamin, -- 1751-1813 -- Correspondence; Bon Homme Richard (Ship); Great Britain. -- Royal Navy -- Officers; President (Frigate); United States. -- Continental Navy -- Officers; United States. -- Navy -- History; United States. -- Navy -- Officers; Merchant ships -- United States; Voyages and travels; Guangzhou (China) -- Description and travel; Mediterranean Sea; New Guinea -- Description and travel; United States -- History -- Tripolitan War, 1801-1805 -- Naval operations; United States -- History, Naval; Naval officers; Naval officers, British